Production of Hydrogen from Seawater as Green Energy using Hydrogen Fuel Generator - Yohandri Bow; Rusdianasari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The decline in crude oil production in Indonesia is a burden for the nation of Indonesia. Therefore, that takes alternative energy or a new innovation is aiming to review the use of fuel oil. One such alternative is hydrogen fuel use (H2). Gas to obtain a review of hydrogen gas can be carried with how to break the air compounds (H2O) into hydrogen gas hydrogen-oxygen (HHO) or brown namely through electrolysis. Electrolysis of water is the decomposition of the compound water into oxygen and hydrogen gas by using an electric current through the water. Current will conduct electricity to the electrodes so that there will be a reduction reaction in the cathode and form hydrogen gas. Speeding up the electrolysis process required an electrolyte solution a solution that conducts electricity. In general electrolysis, processes are undertaken to produce oxygen gas and hydrogen gas using an alkaline solution. The alkaline solution used is a seawater electrolyte. The solution is a strong electrolyte that can conduct electric current well. The electrodes used are stainless steel pipe which is resistant to corrosion with insulating material added cotton fabric that serves as an insulator or barrier zone between the cathode and the anode. By designing a hydrogen fuel generator, hydrogen gas may be generated based on the effect of electric current. Variations of the electrical current used is 3 A, 6 A, 9 A, 12 A, 15 A, 18 A, and 21 A. The higher the electrical current supplied to the production of hydrogen gas will be many more. The production of hydrogen gas is the most widely produced on the current 21 A with 0,0478 LPM of hydrogen gas and efficiency hydrogen fuel generator at 12,9915%.